Automatic Height and Weight Measurement Integrated Database System - uci rahmalisa; Yulisman Yulisman (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Measurement of height and weight, it is needed especially for school age 5-15 years old. From the results of monitoring height and weight measurements, we can monitor whether the child is underweight or overweight and obese. We can also monitor the growth of elementary school age children. The problem faced is that monitoring the growth of children in schools cannot be carried out effectively. This is because the process of measuring children's height and weight is done manually and of course it takes time for the process, besides that, data on student height and weight are also recorded still manually, so that data processing and utilization is not optimal. The purpose of making this Automatic Height and Weight Measurement Integrated Database System to process of measuring height and weight can be done effectively and efficiently, so it can produce integrated information in Database. The existence of an integrated database will make it easier for related parties to recap and archive children's data and store history of children's growth as material for evaluating and monitoring child growth. The results of this evaluation can be used as a reference for follow-up to be conducted. The resulting output is information in the form of tables and graphs of children's growth. In this research using the prototyping method which aims to get an overview of the tool to be designed and built, then it will be evaluated by the user. The evaluated prototype will be used as a reference to make a tool as the final product as the output of this research.